Biology Learning Meets Local Wisdom: Exploring the Ethnopedagogical Value of Bengkulu's Fermented Culinary Tradition "Lemea" for Biology Topics - Hefni Dwika Sari; Siti Sriyati; Widi Purwianingsih (Journal of Innovation in Educational and Cultural Research, 2025)
The Merdeka Curriculum can potentially improve educational standards by fostering appreciation for regional culture and local wisdom. Indonesia's rich cultural heritage offers opportunities to integrate indigenous knowledge into biology education, yet local wisdom remains underexplored in scientific education. This study focuses on the Lemea fermentation tradition of the Rejang Lebong community in Bengkulu, a unique example of local wisdom applicable to the biology curriculum. Using ethnopedagogy, the study bridges the gap between Indigenous and scientific knowledge, aligning with the Merdeka Curriculum's emphasis on character education and cultural appreciation. This literature review, supported by interviews with local experts, examines the scientific relevance of the Lemea fermentation process in topics such as biotechnology, metabolism, bacteria, etc. Interviews with teachers also highlight challenges and opportunities in implementing Lemea as a learning resource. The findings show that the Indigenous knowledge behind Lemea fermentation can be transformed into scientific concepts, supporting high school biology learning outcomes in Phases E and F. This research contributes to the development of ethnopedagogy as an innovative approach and model in science education and offers a model for curriculum design under the Merdeka Curriculum, aligning educational practices with local cultural values to create meaningful and contextual learning experiences.